PENERAPAN PEMBELAJARAN PENDIDIKAN AGAMA HINDU BERBANTUAN VIDEO PADA SISWA SEKOLAH MENENGAH PERTAMA - Pustikayasa, I Made (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Digital transformation is carried out to improve the quality of education and equitable access to education. On the other hand, the character of generation Z and the development of technology are very fast becoming challenges in education. Video-assisted learning in schools is part of digital transformation in education that can motivate students to understand concepts. Based on preliminary observations, SMP Negeri 2 Kahayan Hilir, Pulang Pisau district carried out video-assisted Hindu religious education learning amid limited access to infrastructure and access to technology. The conditions in this school are interesting to explore further to understand the implementation of video-assisted Hindu religious education learning and understand what are the obstacles and efforts made in learning Hindu religious education. This study will be analyzed with cybernetic learning theory. The research method used is a qualitative method to understand the meaning and condition of natural objects in the field. Qualitative data is sourced from observations, interviews, and document studies. The data is then reduced, presented and analyzed qualitatively to understand, explain, interpret, and look for relationships among the data obtained, then draw conclusions and verify. The results showed that video-assisted learning is easier for students to understand according to their respective learning styles. In video-assisted learning, students focus more on the lesson. This result is in accordance with cybernetic learning theory, namely the attention given by students to the lesson will be easier to remember with different learning styles